Differences in Adolescent Confidence in terms of Gender in Adolescents in Medan Tuntungan - Khairuddin (Formosa Journal of Multidisciplinary Research, 2022)
This study aims to determine whether there is a difference in self-confidence of adolescents who are male and female in adolescents in Medan Tuntungan District. The research method used is a comparative quantitative approach, the sample used in this study amounted to 120 adolescents, the sampling technique used in this study was a random sampling technique. Then the data collection using the Likert scale method which is collected through a self-confidence scale which is measured using 6 factors that affect self-confidence. The data analysis technique used by the researcher is the one-way ANOVA analysis technique. Based on the results of the one-way ANOVA calculation, the results obtained are sig (p) = 0.003 < 0.050, which means that the significance value obtained is less than 0.050, which means that there are differences in adolescent self-confidence in terms of male and female sex in adolescents in Medan Tuntungan District. With different hypothetical and empirical mean values, where based on the calculation results, it is found that the self-confidence of male adolescents, the empirical mean = 79.56 < hypothetical mean = 82, where the difference is more than SD = 9.341 so it is in the moderate category, while female adolescents, the empirical mean = 70.12 < hypothetical mean = 82, where the difference is more than SD = 10.224 which is in the moderate category.